Determination of the effect of the bio stimulant (BioProFito) on the water-physical properties of the soil in the conditions of the saline soils of the Bukhara oasis (Texas Journal of Agriculture and Biological Sciences, 2024)
The article presents the comprehensive results of a research study aimed at determining the impact of the biostimulant BioProFito on the water-physical properties of soil in the saline conditions of the Bukhara oasis. The study was conducted on an experimental field where BioProFito was applied, and meticulous monitoring was carried out at both the beginning and the end of the growing season across various test variants. The research focused primarily on observing changes in the volumetric weight of the soil, which is a crucial indicator of soil compaction and overall health. The findings revealed that the volumetric weight of the soil ranged between 1.31 to 1.29 g/cm³. This slight but significant reduction indicates an improvement in soil structure, potentially enhancing root penetration and water retention capabilities. The integration of biostimulants with drip irrigation technology showed promising results. Enhanced water permeability was observed, indicating that the soil’s ability to absorb and distribute water had improved. This is particularly beneficial for cotton cultivation, which requires consistent moisture levels for optimal growth. The combination of these technologies not only supports better crop yields but also contributes to the sustainability of agricultural practices in challenging environments